Western North Carolina Its Mountains and Its People to 1880 - Blackmun, Ora (Appalachian State University, 1977)
Published in 1977, Western North Carolina is a narrative history of the Southern Appalachian Mountains up to 1880. Ora Blackmun depicts the stories of native Cherokee and Sequoyah people and pioneers such as William Bartram, Daniel Boone, Bishops Spangenberg and Asbury, and Zeb Vance.